1982
DOI: 10.1073/pnas.79.9.3047
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal oxidative metabolism of estradiol in women with breast cancer.

Abstract: The three dominant oxidative biotransformations of estradiol were examined in 10 normal women and 33 females with breast cancer by using a recently devised radiometric method. Estradiol tracers, labeled with 3H specifically in the 17a, C-2, or 16a position, were used to measure both the rate and extent of 17P-ol oxidation (the initial metabolic step) and the subsequent 2-and 16a-oxidative reactions. The mean ± SEM values for the extent of estradiol metabolism at these three specific sites were 76.9 ± 5.3%, 31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(113 citation statements)
references
References 29 publications
6
106
0
1
Order By: Relevance
“…CYP3A4 catalyzes the hydroxylation of estrogen to two active metabolites, at least one of which has been associated with mammary tumors in rodents 34 and humans. 35,36 In addition, CYP3A enzymes are involved in the activation of numerous environmental pro-carcinogens into their active carcinogenic forms, making a role for CYP3A variation in cancer susceptibility biologically plausible. 37 However, the results of association studies of CYP3A variation and breast cancer risk are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A4 catalyzes the hydroxylation of estrogen to two active metabolites, at least one of which has been associated with mammary tumors in rodents 34 and humans. 35,36 In addition, CYP3A enzymes are involved in the activation of numerous environmental pro-carcinogens into their active carcinogenic forms, making a role for CYP3A variation in cancer susceptibility biologically plausible. 37 However, the results of association studies of CYP3A variation and breast cancer risk are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Fatness is associated with an increased extraglandular conversion of androgen to oestrogen (Grodin et al, 1973;Forney et al, 1981;Siiteri, 1981) and the metabolism of oestrogen to more potent forms, (Fishman et al, 1975) which have been observed in association with breast cancer (Schneider et al, 1982;Bradlow et al, 1983). Also, excess body weight is associated with a diminished capacity of serum sex-hormone-binding globulin and an elevated percentage of serum oestradiol in the free state (Siiteri, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens have been proposed to induce carcinogenesis by multiple mechanisms including covalent modification of the estrogen receptor (110,111), induction of chromosomal abnormalities (112,113), an epigenotoxic mechanism (114), conversion of 17β-estradiol to catechol estrogens and redoxactive and adduct-forming estrogen quinones (108,115), and subsequent ROSmediated DNA damage (116,117).…”
Section: Cancermentioning
confidence: 99%